mdm-miR828 Participates in the Feedback Loop to Regulate Anthocyanin Accumulation in Apple Peel - Zhang, Bo; Yang, Hui-Juan; Yang, Ya-Zhou; Zhu, Zhen-Zhen; Li, Ya-Nan; Qu, Dong; Zhao, Zheng-Yang (Frontiers in Plant Science, 2020)
Anthocyanins are responsible for the red pigmentation in the peel of apple (Malus × domestica Borkh.) fruit. Relatively few studies have investigated anthocyanins at the post-transcriptional level. MicroRNAs play an important role in plant growth and development by regulating gene expression at the post-transcriptional level. In this study, mdm-miR828 showed a relatively low expression level during the rapid fruit coloration period. However, the mdm-miR828 expression level increased in the late fruit coloration stage. Overexpression of mdm-miR828 inhibited anthocyanin synthesis in apple and Arabidopsis. Dual-luciferase and yeast one-hybrid assays showed that MdMYB1 is capable of binding to the promoter of mdm-MIR828b to promote its expression. The results indicate that mdm-miR828 is involved in a feedback regulatory mechanism associated with anthocyanin accumulation in apple. In addition, mdm-miR828 may be involved in the inhibition of anthocyanin accumulation in response to high temperature.